2019
DOI: 10.1177/0361684319851718
|View full text |Cite
|
Sign up to set email alerts
|

Body-, Eating-, and Exercise-Related Comparisons During Eating Disorder Recovery and Validation of the BEECOM-R

Abstract: Social comparison tendencies are strongly associated with body dissatisfaction and disordered eating. In the current study, we quantitatively examined the structure and predictive value of these constructs during eating disorder recovery. We revised an existing measure of body-, eating-, and exercise-related social comparisons, the Body, Eating, and Exercise Comparison Orientation Measure (BEECOM), to improve psychometric properties. We also assessed the psychometric properties of the shortened Body, Eating, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
1
12
0
1
Order By: Relevance
“…Findings from several research studies have been consistent in supporting the psychometric properties of the BEECOM scores in terms of both reliability and convergent/incremental validity [ 14 , 16 , 17 , 18 ]. In contrast, the available evidence on the factorial validity of the instrument is far less conclusive.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Findings from several research studies have been consistent in supporting the psychometric properties of the BEECOM scores in terms of both reliability and convergent/incremental validity [ 14 , 16 , 17 , 18 ]. In contrast, the available evidence on the factorial validity of the instrument is far less conclusive.…”
Section: Introductionmentioning
confidence: 53%
“…A cognitive process that has been consistently identified as a modifiable risk factor for ED is the tendency towards body/appearance-related social comparison [ 9 , 10 , 11 , 12 ]. However, an emerging line of research has begun to demonstrate that further consideration of comparisons focused on actions aimed at improving body appearance, such as eating or exercise behavior, may provide deeper insight into the cognitive processes underlying ED [ 13 , 14 , 15 , 16 ]. This body of research has been built around the only self-reported quantitative measure proposed to date for the purpose of assessing the three facets of ED-related social comparisons outlined above (i.e., the Body, Eating, and Exercise Comparison Orientation Measure, BEECOM) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BETR program is designed to specifically serve the needs of patients struggling with BESD. A case report suggested that having patients with BESD participate in treatment programs designed primarily for restrictive eating disorders may be problematic due to differing foci of weight restoration versus normalizing eating patterns, as well as patients’ comparisons to other patients, which can be detrimental to recovery [ 24 , 25 ]. Although there is little empirical evidence to support this, a study of intensive treatment specifically for patients reporting episodes of overeating (patients with BN, BED, or obesity without binge eating) found improvements in eating disorder psychopathology after 5 weeks, suggesting that targeted specialty care may be more effective and more efficient than general eating disorder treatment programs that address a wide range of symptomatology [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Por outro lado, pode-se identificar no contexto de pandemia um potencial de mitigação dos gatilhos sociais interpessoais relacionados à comportamentos alimentares tidos como desordenados e insatisfação corporal como consequência, por exemplo, da redução de oportunidades para comparações sociais baseadas no corpo (Cooper et al, 2020;Saunders et al, 2019).…”
Section: Introductionunclassified